2019
DOI: 10.1016/j.neuro.2019.02.016
|View full text |Cite
|
Sign up to set email alerts
|

Chronic, low-level oral exposure to marine toxin, domoic acid, alters whole brain morphometry in nonhuman primates

Abstract: Domoic acid (DA) is an excitatory neurotoxin produced by marine algae and responsible for Amnesiac Shellfish Poisoning in humans. Current regulatory limits (~0.075-0.1 mg/kg/day) protect against acute toxicity, but recent studies suggest that the chronic consumption of DA below the regulatory limit may produce subtle neurotoxicity in adults, including decrements in memory. As DA-algal blooms are increasing in both severity and frequency, we sought to better understand the effects of chronic DA exposure on repr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 70 publications
0
14
0
Order By: Relevance
“…The data from this study show the reduction in the degree of differentiation of rNSC into all three type of cells and the reduction in axonal length of neurons in the presence of low non-cytotoxic concentration of DA (0.05 μM). Data from rodents and non-human primates have shown that non-cytotoxic low dose exposure to DA during early life was associated with behavioral, memory deficits, and/or structural changes in the brain [47,48,49,50,51,52]. This memory loss may be linked to a reduction and/or the abnormal differentiation of neural stem cells.…”
Section: Discussionmentioning
confidence: 99%
“…The data from this study show the reduction in the degree of differentiation of rNSC into all three type of cells and the reduction in axonal length of neurons in the presence of low non-cytotoxic concentration of DA (0.05 μM). Data from rodents and non-human primates have shown that non-cytotoxic low dose exposure to DA during early life was associated with behavioral, memory deficits, and/or structural changes in the brain [47,48,49,50,51,52]. This memory loss may be linked to a reduction and/or the abnormal differentiation of neural stem cells.…”
Section: Discussionmentioning
confidence: 99%
“…Such a pattern has been observed previously in human patients with mTLE (Concha et al ., 2010; Dinkelacker et al ., 2015; Otte et al ., 2012). Diffusion MRI has also been used to study chronic, low-level DOM exposure in live macaques (Petroff et al 2019), and preliminary evidence indicates altered white matter parameters in the fornix as well as the internal capsule.…”
Section: Methodsmentioning
confidence: 99%
“…Ongoing studies with laboratory primates suggest delayed developmental effects occur in primates exposed in utero , but these findings will take several years to confirm, and due to expense, are of limited sample sizes (Burbacher et al . 2019, Petroff et al . 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Adult humans acutely exposed to DomA developed sensorimotor neuropathy and axonopathy as assessed by electromyography (Teitelbaum et al, 1990). A subset of primates exposed orally at or near the accepted daily tolerable dose of 0.075 mg/kg developed visible hand tremors (Petroff et al, 2019). Rodents prenatally exposed to DomA (PND 10-17) developed aberrant gait patterns (Shiotani et al, 2017).…”
Section: Implications For Human Healthmentioning
confidence: 99%